2019
DOI: 10.1111/vsu.13244
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum and synovial leptin concentrations with body condition scores in healthy and osteoarthritic dogs

Abstract: Objective To evaluate the relationship between serum and synovial fluid (SF) leptin concentrations and body condition score (BCS) in healthy and osteoarthritic dogs. Study design Controlled, prospective, clinical study. Animals Nineteen healthy dogs and 29 dogs with osteoarthritis (OA) secondary to cranial cruciate ligament injury. Methods Synovial fluid was obtained from the femorotibial joint under sedation (healthy dogs) or during surgery (OA dogs). Serum and SF leptin and interleukin (IL)‐1β concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…28 29 Adipokines including leptin are produced by adipose cells and are directly related to body condition scores and the development and progression of osteoarthritis. 30 31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 29 Adipokines including leptin are produced by adipose cells and are directly related to body condition scores and the development and progression of osteoarthritis. 30 31…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Adipokines including leptin are produced by adipose cells and are directly related to body condition scores and the development and progression of osteoarthritis. 30,31 Normalizing GRF based only on body weight may not be sufficient for analysing dogs of different breeds as body configuration may also play a role in differences in GRF. Several studies have reported variations in GRF among different breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of leptin, which reflect body fat mass, are increased in overweight cats, dogs and humans, 76 and the proinflammatory role of leptin in the development of DJD has been established in humans 77 and dogs. 73 , 74 , 78 , 79 Although there is a paucity of studies investigating the role of mechanical and biochemical factors in the relationship between obesity and feline DJD, it is possible that these postulations could also apply to cats.…”
Section: Discussionmentioning
confidence: 99%
“…Они представляют из себя анкеты (questionnaire), которые заполняет владелец животного или клиницист. Наиболее распространёнными являются Health Risk Assessment (HRA), Canine Brief Pain Inventory (CBPI), Helsinki Chronic Pain Index (HCPI), Liverpool Osteoarthritis in Dogs (LOAD), Canine Orthopedic Index (COI), Feline Musculoskeletal Pain Index (FMPI) [4][5][6].…”
Section: результаты исследования и их обсуждениеunclassified